Analyzing the Performance of Construction Demolition Waste Aggregates on strength for Non-structural Concrete - Dhungana, Sunil; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.004 Construction and demolition waste (CDW) refers to the waste generated from demolished structures in the construction industry. This waste can include concrete and brick materials. In this study, the focus is on evaluating the physical and mechanical properties of coarse aggregates derived from CDW, as well as the compressive strength of non-structural concrete made by mixing CDW aggregates with natural aggregates (NA) in different proportions. The study involved preparing different mix proportions of concrete using various combinations of CDW coarse aggregates, natural coarse aggregates, and brick aggregates. The mix proportions were categorized into three groups:100% natural coarse aggregate,CDW concrete coarse aggregate mixed with natural aggregate in three proportions: (90% NA, 10% CA), (80% NA, 20% CA), and (60% NA, 40% CA) and Mixtures of natural coarse aggregate, CDW concrete aggregate, and brick aggregate in four proportions: (90% NA, 5% CA, 5% BA), (80% NA, 10% CA, 10% BA), (60% NA, 20% CA, 20% BA), and (80% NA, 30% CA, 30% BA). The physical and mechanical properties of the different mix proportions were analyzed, and it was found that all proportions, except (80% NA, 30% CA, 30% BA), met the specified limits. In terms of compressive strength, the concrete mixture with a proportion of (90% NA, 10% CA) exhibited the highest value (27.04 MPa), while the mixture with a proportion of (60% NA, 20% CA, 20% BA) had the lowest value (17.19 MPa). The mixture with a proportion of (80% NA, 30% CA, 30% BA) did not meet the targeted strength of 15 MPa. Conclusion: Based on the analysis of the test results, it can be suggested that CDW aggregates can be used as a replacement for natural aggregates up to a maximum of 40%. Additionally, a combination of CDW concrete and brick aggregates in equal proportions (20% - 20%) can be used as a replacement for natural aggregates to achieve a concrete strength of 15 MPa.